2021
DOI: 10.1002/hpja.464
|View full text |Cite
|
Sign up to set email alerts
|

Online retail promotion of e‐cigarettes in New Zealand: A content analysis of e‐cigarette retailers in a regulatory void

Abstract: In New Zealand [NZ], electronic-cigarettes [e-cigarettes] are available at specialist e-cigarette stores, traditional tobacco retailers and through online stores. Online sales data are not readily available in NZ 1 ; however, other high-income countries highlight the significance of online retailing. For example, the United States reports that internet sales of e-cigarettes account for 30% of total sales. 2 It is expected that online sales have increased during the COVID-19, as many physical retail outlets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Nevertheless, despite the evidence of short-term effects of e-cigarette use their long-term health impacts are not known. Celebrity endorsements were reported in previous studies [14,16], presence of doctors [14] and cartoon pictures [17].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Nevertheless, despite the evidence of short-term effects of e-cigarette use their long-term health impacts are not known. Celebrity endorsements were reported in previous studies [14,16], presence of doctors [14] and cartoon pictures [17].…”
Section: Discussionmentioning
confidence: 62%
“…In addition, the claims about affordability, convenience, are aimed to encourage uptake of e-cigarette by the non-smoking youth and young adults by making ecigarette appear as healthier, less risky, and socially appealing. Therefore, websites mostly did not have strict checks to prevent access to minors as in previous studies about e-cigarette websites [17]. Review of published research has shown that most of the YouTube and Instagram have content that promotes ecigarette use but seldom not contain age and/or health warnings [25].…”
Section: Marketing Claims Reported Bymentioning
confidence: 98%
See 2 more Smart Citations
“…The industry group also drew on more tobacco industry-funded sources, consistent with previous research findings [ 19 , 20 ]. Whilst smaller e-cigarette companies in this study provided a small portion of supporting evidence compared to tobacco companies, research demonstrates that e-cigarette retailers in NZ regularly present scientific claims in promotional material [ 21 ] and therefore should have this data available to cite.…”
Section: Discussionmentioning
confidence: 99%